THE SCRUM GUIDANCE FOR IT SERVICE SUPPORT DOMAIN AND SQA TO GENERATE SUCCESSFUL AND QUALITY SOFTWARE - Fitria, Rahma (Jurnal Teknologi Terapan and Sains 4.0, 2021)
The article is presenting how to implement the framework of scrum in IT service support domain and software quality assurance (SQA). Basicly, scrum framework is being used in other software development methods such as agile, but the reseach found that there is merely a few could support the software development. This framework could be implemented in small, medium and large projects. By promoting the usage of scrum framework could add more valu to organization and reach its goal. The collection of scrum framework implementation from previous researcher could present the real example of scrum framework in IT service domain and SQA. As this framework is still new in practice to IT domain, so that the guidance of this scrum framework will help developer to have more experience in applying in any software development projects. As the result, the company will enhance their business value